A Two Unit Standby System with Preventive Maintenance and Inverse Gaussian Repair Time Distribution - Gupta, Rakesh; Sharma, Vishal (Journal of Informatics and Mathematical Sciences, 2010)
The present paper deals with the profit function analysis of a two identical unit standby system model with the concept of preventive maintenance of the operative unit after some significant time that is not fixed. Time to preventive maintenance and preventive maintenance time are considered correlated and their joint distribution is taken as bivariate exponential. The failure time distribution of an operative unit is taken as exponential whereas the repair time distribution is inverse gaussian. The system model has been analyzed by using regenerative point technique. The graphical behaviors of MTSF and profit function have also been studied.